A multi‐institutional analysis of children on long‐term non‐invasive respiratory support and their outcomes. Issue 4 (17th January 2018) - Koncicki, Monica L.; Zachariah, Philip; Lucas, Adam R.; Edwards, Jeffrey D.
Abstract: Objectives: To characterize a multi‐institutional cohort of children with chronic respiratory failure that use long‐term, non‐invasive respiratory support, perform a time‐to‐event analysis of transitions to transtracheal ventilation and identify factors associated with earlier transition to transtracheal ventilation. Study Design: A retrospective cohort study of patients less than 21 years of age with diagnoses associated with chronic respiratory failure and discharged on non‐invasive respiratory support was performed using data from the Pediatric Health Information System (PHIS) between 2007 and 2015. Demographic and clinical characteristics, as well as times from index discharge on non‐invasive support to transtracheal ventilation were presented. A competing risk regression model was fitted to estimate factors associated with earlier transition to transtracheal ventilation. Results: A total of 3802 patients were identified. Their median age at index discharge was 10.4 years (interquartile range [IQR] 4.1‐14.9). Of these patients, 337 (8.9%) transitioned to transtracheal ventilation and transitioned at a median of 11.5 months (IQR 4.6‐26) post‐index discharge, or a median age of 9.3 years (IQR 4.2‐14.5). Competing risk modeling demonstrated that patients who were older or whose discharge occurred later in the study period had lower hazards of earlier transition to transtracheal ventilation, whereas patients with anoxia/encephalopathy and quadriplegia had higher hazards of earlier transitioning. Conclusions: Most patients on long‐term, non‐invasive respiratory support who progress to transtracheal ventilation transition do so within a few years of support initiation. Various characteristics were associated with earlier risk of transitioning to transtracheal ventilation. This information may enhance anticipatory guidance for this population.